Study In The Relationship Among Price, Rating, Popularity, And Size Multimedia Application In Play Store: Studi tentang Hubungan antara Harga, Rating, Popularitas, dan Ukuran Aplikasi Multimedia di Play Store - Sudaryanto, Aninditawidagda Pandam; Basiroh, Basiroh; Rahmadzani, Rifqi Fauzi (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
Abstrak This study examines the relationship between price, rating, popularity (number of downloads), number of features, and the size of multimedia applications on the Google Play Store. These factors are important as they influence each other and affect the appeal and success of applications in the digital marketplace. Applications that are too large in size may hinder the download process, while an unbalanced number of features can reduce user convenience. This research employs web scraping techniques to collect data from the Google Play Store, which are then analyzed using Spearman and Pearson correlation tests. The results indicate that for paid applications, only size and the number of features have a significant correlation. Meanwhile, for free applications, size is significantly correlated with the number of downloads, ratings, and number of features. Application size and rating show a moderately strong relationship, with Spearman and Pearson coefficients of -0.302 and -0.277, respectively. These findings highlight the importance of balancing size, features, and user perception in formulating application development strategies. This study contributes to developers and researchers by providing insights into the dynamics of application attributes that influence user acceptance and supports more informed decision-making in digital application development.